2020
DOI: 10.1136/bmjdrc-2020-001268
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes knowledge, risk perception, and quality of life among South Asian caregivers in young adulthood

Abstract: IntroductionPersons of South Asian descent have a higher prevalence of type 2 diabetes mellitus (T2DM). The management of T2DM in the South Asian community has required the support of adult children, potentially impacting the quality of life, diabetes-related knowledge, and risk perception among these caregivers.Research design and methodsTo investigate diabetes-related knowledge, quality of life, risk perception, and actual risk of developing diabetes among South Asian young adults whose parents are living wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Among those who had family history of diabetes, 27.52% [ 22 ], 34.2% [ 14 ] and 62.7% [ 36 ] perceived high risk of developing type 2 diabetes. A randomized controlled trial conducted among individuals with family history of diabetes found that 34.6% of those in the intervention group and 40.6% of those in the control group perceived their risk of diabetes to be likely or very likely [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those who had family history of diabetes, 27.52% [ 22 ], 34.2% [ 14 ] and 62.7% [ 36 ] perceived high risk of developing type 2 diabetes. A randomized controlled trial conducted among individuals with family history of diabetes found that 34.6% of those in the intervention group and 40.6% of those in the control group perceived their risk of diabetes to be likely or very likely [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting the importance of risk perception in influencing health-related behaviours, many studies have been conducted to assess the level of risk perception of NCDs including diabetes [ 13 , 14 ]. The level of risk perception from these studies varies, probably due to difference in study population and tools used to measure the risk perception of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…5 This type of risk perception increases in women, those who are older, have a family history of diabetes, are overweight/obese, consume sugary drinks, do not consume fruits and vegetables, have a previous diagnosis of hypertension, have knowledge about the risk factors for T2DM and have a poor perception of their health status. [6][7][8][9][10] However, a study conducted in Alemannia, reports that people with prediabetes and undiagnosed T2DM report low risk perception, 11 the same as in the Mexican population. 12 The low risk perception of T2DM may be due to different factors such as beliefs that diseases are unpredictable, or fatalistic beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…As patients' physical functions decline due to their increased age, the management of diabetes is challenging (7). In addition, as long-term lifestyle interventions in diabetic patients continue, patients' perception of risk factors can decrease due to a lack of tools to objectively measure these factors, resulting in decreased motivation and compliance (8). These two problems interact synergistically, significantly affecting the management of CCVCs of T2DM.…”
Section: Introductionmentioning
confidence: 99%